A fertile male with cystic fibrosis: molecular genetic analysis. Issue 6 (June 1991) - Barreto, C; Pinto, L M; Duarte, A; Lavinha, J; Ramsay, M
Abstract : A family study is presented in which the father of a girl with severe cystic fibrosis (CF) was also found to have CF but was mildly affected. He was diagnosed with three positive sweat tests including one after suppression with fludrocortisone. Genetic analysis showed that he is a compound heterozygote with the delta F508 CF mutation associated with haplotype B and a second CF mutation associated with haplotype C. In this unusual, fertile CF male, the late age of diagnosis (30 years) and the mild clinical picture suggest that the compound genotype (delta F508/other CF mutation) determines a much less severe form of the disease which might have gone unnoticed in the absence of a severely affected child. The implications of these findings for genetic counselling of families with CF are discussed.